The Knowledge of Traditional Medical Treatment (Namalo) in Batak Toba Community (at Tambunan Lumban Gaol Village, Balige District, Toba Samosir Regency) - Sinambela, G.Z. Sarah Magdalena; Agustrisno, (Indonesian Journal of Medical Anthropology, 2021)
This study examines the knowledge of Traditional Medical treatment (Namalo) in Toba Batak community at Tambunan Lumban Gaol Village. The purpose of this study was to determine the process of traditional medical treatment by Namalo and to know the perception of the community regarding traditional medical treatment performed by Namalo. In this research, the method used is ethnographic method and uses a qualitative approach to see the phenomenon of traditional medical treatment, especially Namalo, with data collection techniques through in-depth interviews and observations, where the authors go directly to the field to obtain accurate information from the community. The results of the study show that the traditional treatment carried out by Namalo is still visited by many people today because it does not conflict with religious teachings and traditional medical treatment is more affordable than medical treatment. Traditional medical treatment is a health effort in a different way from medical science, rooted in traditions derived from habits by previous ancestors. We need to preserve traditional medical treatment and continue to develop it because it is beneficial for society.